Representasi Standar Kompetensi Guru dalam Anime Ansatsu Kyōshitsu (Kajian Semiotika dan Sosiologi Pendidikan) - Tri Ambarwati; Subhan Widiansyah (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2023)
This article aims to explain teacher competency standards in Anime Ansatsu Kyōshitsu.  Education is one of the things that is very important for human life, therefore humans will not be able to escape from the obligation to receive education, even until the end of his life.  The human factor that plays a very important role in education is the teacher, who is the main way in providing insight to students.  Along with the times, education can be found anywhere, including films that were fun to watch at first.  Film has various types, one of which is a film that is packaged in the form of animation.  In Japan itself, the animation has a special name, namely "Anime".  In this article, the method used is descriptive qualitative using content analysis and Charles Sanders Pierce's semiotic approach.  The anime that is the subject of analysis is Anime Ansatsu Kyōshitsu by Yūsei Matsui.  In the Ansatsu Kyōshitsu anime, several teacher competency standards are found, namely professional competence, pedagogical competence, social competence, and personality competence.